Current practices in physical fitness assessment and monitoring among coaches of individual and team sports: a survey in Portugal, Spain, and Romania - Wen, X.; Silva, R. M.; Xu, Q.; González-Fernández, F. T.; Silva, A. F.; Badicu, G.; Guo, X.; Clemente, F. M. (Biology of Sport, 2024)
The objective of this study was to characterize surveyed coaches and elucidate the practices of physical fitness assessment and monitoring for both male and female athletes across three countries. A total of 165 coaches participated by completing a comprehensive 32 question survey. Pre-season assessments are a priority for coaches, with a significant range from 60.5% to 87.7% in Romania, while Portuguese and Spanish coaches tend to prefer testing during the competition (26.3% and 16.9%, respectively). Portuguese and Spanish coaches predominantly favor aerobic tests (50% and 46.8% respectively), whereas Romanian coaches exhibit a preference for sprint (56.9%) and skill tests (52.3%). Notably, change of direction tests are less commonly employed, ranging from 10.5% to 21% across the countries. In terms of exercise intensity determination, Portuguese coaches predominantly employ maximal heart rate (31.6%), while Spanish coaches often rely on the 220-age formula or perceived exertion (27.4%). For strength assessment, Portuguese coaches lean towards direct (34.2%) or estimated (31.6%) maximal repetition methods. When it comes to maximal speed sprint, Portuguese and Romanian coaches show preference (50% and 43.1% respectively), while Spanish coaches exhibit a relative lack of emphasis on individualized speed measures (37.1%). Perceptual scales are the preferred method for recovery monitoring, with adoption rates of 57.9% in Portugal, 53.2% in Spain, and 44.6% in Romania. In summary, this study underscores the distinct assessment and monitoring practices employed by coaches in Portugal, Spain, and Romania. These findings are in alignment with established literature standards, highlighting the diversity of approaches used in different countries.